Denial of a fair trial - does a trial in absentia constitute as denial of a fair trial - Owino, Eunice Anyango (Strathmore University, 2019)
A fair trial is one of the most fundamental right that the judicial system can give an accused person to a criminal trial. This is due to the fact that the violation of the right to a fair trial my render the whole trial process unjust. A trial in absentia on the other had means that the accused person was absent from This dissertation seeks to show that in absentia trials are in themselves a violation of the right to a fair trial, the right of the accused person to be present during their own trial therefore accommodations should be made for the accused person to be present during their trial.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Fair trial; Judicial system; Criminal trial; Trial in absentia